State Responsibility to Provide a Free Legal Aid Access for the Poor and the Obstacles in the Implementation - Kesuma, Derry Angling (The Indonesian Journal of International Clinical Legal Education, 2019)
Access for the Poor to receive legal aid include in the area of criminallaw, Civil and Administrative-State, both litigation and nonlitigation.Legal Aid Litigation includes (1) Criminal cases, includinginvestigations, and trials in court I, appellate court, appellate hearings,and review; (2) Civil cases, including peace efforts or court decisions I,appellate court judgments, appellate court decisions, and review; and;(3) State administrative cases, including preliminary hearings and courtdecisions I, appellate court judgments, appellate court decisions, andreview. Obstacles and Constraints In the realization of Free LegalAssistance for People Not being able to factor their own lawenforcement officers is that the investigator who did not give the rightof suspects to legal assistance free of charge as mentioned in Article 56of the Criminal Procedure Code. Apparatus enforcer law ignoreobligations for pointed advisor law on free more caused becausein rules law we no juridical consequences that includes sanctions forinvestigators if not to say the rights of the suspect when theinvestigation or at all level examination. There are also constraints inproviding access to free legal aid for poor people, namely: a) lack ofsufficient budget for legal aid freely, b) In the constrained legal aiddisbursement by the certificate cannot afford, c) the defendant balks tobe accompanied legal advisors, d) There is still a court that has not hada POSBAKUM so that the Court finds it difficult to order a legal counselwho is willing to assist the defendant; e) Honors received by a relativelysmall legal counsel, f) A legal counsel appointed to assist a defendantwho is not able to be reluctant or often does not attend the hearingand does not appoint a replacement; g) If a defendant is unable toprepare a certificate of incapacity, because the defendant or theapplicant is in custody and they are not even domiciled or non-residentwithin the jurisdiction. This will result in the difficulty of disbursing thelegal aid funds